Voltammetric determination of heparin based on its interaction with malachite green - Xueliang Niu; Weili Zhang; Na Zhao; Wei Sun (Bulletin of the Chemical Society of Ethiopia, 2008)
In this paper malachite green (MG) was used as a bioprobe to determine heparin concentration by linear sweep voltammetry on the dropping mercury working electrode (DME). In Britton-Robinson (B-R) buffer solution of pH 1.5, MG had a well-defined second order derivative linear sweep voltammetric reductive peak at –0.618 V (vs. SCE). After the addition of heparin into the MG solution, the reductive peak current decreased apparently without the movement of peak potential. Based on the difference of the peak current, a new voltammetric method for the determination of heparin was established. The conditions for the binding reaction and the electrochemical detection were optimized. Under the selected experimental conditions the difference of peak current was directly proportional to the concentration of heparin in the range from 0.3 to 10.0 mg/L with the linear regression equation as ∆ip″ (nA) = 360.19 C (mg/L) + 178.88 (n = 15, γ = 0.998) and the detection limit as 0.28 mg/L (3σ). The effects of coexisting substances such as metal ions, amino acids on the determination of heparin were investigated and the results showed that this method had good selectivity. This method was further applied to determine the heparin content in heparin sodium injection samples with satisfactory results and good recovery. The stoichiometry of the biocomplex was calculated by the electrochemical method and the binding mechanism was further discussed.